2019
DOI: 10.3390/nu11092082
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of β-Hydroxy-β-Methylbutyrate (HMB) Supplementation in Addition to Physical Exercise in Older Adults: A Systematic Review with Meta-Analysis

Abstract: Both regular exercise training and beta-hydroxy-beta-methylbutyrate (HMB) supplementation are shown as effective treatments to delay or reverse frailty and reduce cognitive impairment in older people. However, there is very little evidence on the true benefits of combining both strategies. The aim of this meta-analysis was to quantify the effects of exercise in addition to HMB supplementation, on physical and cognitive health in older adults. Data from 10 randomized controlled trials (RCTs) investigating the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
1
33
1
1
Order By: Relevance
“…Force and Fatigue. HMB has been shown to improve strength and fatigue resistance in quadriceps muscles of humans including the elderly in multiple studies especially when HMB treatment was combined with exercise [53,95,103,[126][127][128][129][130]. However, we did not observe an increase in muscle force or fatigue resistance in the EDL muscles of Ca-HMB-treated rats after unloading by HS or during reloading as compared to rats that received water.…”
Section: Edl Musclecontrasting
confidence: 85%
See 1 more Smart Citation
“…Force and Fatigue. HMB has been shown to improve strength and fatigue resistance in quadriceps muscles of humans including the elderly in multiple studies especially when HMB treatment was combined with exercise [53,95,103,[126][127][128][129][130]. However, we did not observe an increase in muscle force or fatigue resistance in the EDL muscles of Ca-HMB-treated rats after unloading by HS or during reloading as compared to rats that received water.…”
Section: Edl Musclecontrasting
confidence: 85%
“…In this study, we found that Ca-HMB was unable to change EDL mass or function or decrease apoptotic signaling in response to HS or R in aged rats. While multiple studies have shown that Ca-HMB was beneficial by suppressing pathways associated with muscle wasting and aging in the plantar flexor muscles (gastrocnemius, plantaris, and soleus muscles) of rodents [43,51,60,62] and in the limb muscles of humans [53,59,80,95,103,[126][127][128][129][130]141], other studies suggest that Ca-HMB could not reverse a decline in muscle function, mitochondria protein synthesis, or anabolic signaling in limb muscles with aging [136,153,154]. However, it is also possible that even though HMB might not improve muscle mass or function in aging, other benefits such as improved cognitive function which were not measured in the current study could be achieved [154].…”
Section: Discussionmentioning
confidence: 99%
“…10 However, the beneficial effects of HMB supplementation combined with exercise to preserve muscle mass and function in older adults are not well investigated. 11 Thus, this clinical trial can provide a better understanding of the effectiveness of combined treatment in managing sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review with meta-analysis by Courel-Ibáñezet al reported that the effect of HMB supplementation in addition to physical exercise was not significant on improving muscle strength or physical performance in adults aged 50-80 years compared with exercise alone. 11 This conclusion was drawn based on 10 RCTs that involved healthy and younger subjects from 50 years of age, with heterogeneous dosages of HMB supplement and exercise programmes. However, very few data exist that test the combined effects of HMB and exercise on the musculoskeletal health in older, frailer or sarcopenic people.…”
Section: Open Accessmentioning
confidence: 99%
“…In fact, a recent meta-analysis revealed a small significant effect for HMB supplementation on increasing muscle mass and function in a variety of clinical conditions characterized by loss of skeletal muscle mass and weakness [45]. However, older subjects performing physical activity seem not to have further benefits on physical function by ingesting HMB when compared to performing physical activity only [46]. Finally, the ingestion of HMB by subjects performing non-resistance exercise activities might also produce distinct results when compared to our conclusions since a few trials have shown significant changes in body composition and performance variables as an effect of HMB supplementation [47,48].…”
Section: Discussionmentioning
confidence: 99%